Konsep Penerapan Wanprestasi dan Perbuatan Melawan Hukum (PMH): Studi Kasus Putusan Nomor 79/ Pdt.G/2023/PN Yyk - Danis, Ananda Harfa (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
This study analyze the application of the concepts of breach of contract (wanprestasi) and unlawful act/ tort (perbuatan melawan hukum) in decision No. 79/Pdt.G/2023/PN. Yyk, with critical focus on the panel of judges formalistic approach. The research employs a normative method through a case study approach. The results indicate that although the plaintiff’s lawsuit was declared inadmissible due to formal defect (obscuur libal and plurium litis consortium), the cout proceedings actual revealed strong indications of an unlawful act by the defendant, namely the installation of “for sale/ rent” banner on a property that was still under lease. Theoretically, this action fulfills the elements of acticle 1365 of the indonesian civil code. The study concludes that the judge was incorrect in ther role as a seeker of substantive justice by fixaing on procedural rigiditly and neglecthing the principle of ius curia novit. Therefore, this research recommends the necessity of balancing formal legal certainty with the achievement of material justice in civil court practices.